2021
DOI: 10.1021/acsami.1c13647
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of Au-Glycopolymer Nanoparticles for Surface-Enhanced Raman Scattering-Based Biosensing and Single-Cell Immunity

Abstract: Successful synthesis of glyconanoparticles has attracted much attention due to their various biointeractive capabilities, but it is still a challenge to understand different single-cell responses to exogenous particles among cell populations. Herein, we designed polyaniline-containing galactosylated gold nanoparticles (Au@PGlyco NPs) via in situ polymerization of ortho-nitrophenyl-β-galactoside assisted by Au nucleation. The nanogold-carrying polyaniline block produced electromagnetic enhancement in surface-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
(155 reference statements)
0
11
0
Order By: Relevance
“…EDS mapping analysis (Figure S3a) showed that the N and Fe elements of the organic materials were colocalized around the surface of a Au nanorod (Figure S3b,c) and also appeared within its body area. Compared with Au solid particles in the TEM measurement (Figure f), an increase in the hydrodynamic diameter of the particles (Figure S4) was attributed to the existence of an organic coating on the surface of the Au nanorods …”
Section: Resultsmentioning
confidence: 95%
“…EDS mapping analysis (Figure S3a) showed that the N and Fe elements of the organic materials were colocalized around the surface of a Au nanorod (Figure S3b,c) and also appeared within its body area. Compared with Au solid particles in the TEM measurement (Figure f), an increase in the hydrodynamic diameter of the particles (Figure S4) was attributed to the existence of an organic coating on the surface of the Au nanorods …”
Section: Resultsmentioning
confidence: 95%
“…According to another work, Chia et al [ 126 ] created polyaniline (PANI)-containing glycopolymer gold nanoparticles (Au@PGlyco NPs) by in situ polymerization of ortho-nitrophenyl- β -galactoside with the assistance of Au nucleation. An electromagnetic boost in surface-enhanced Raman scattering (SERS) was seen when the nano-Au-carrying polyaniline block was used.…”
Section: Glycopolymer-based Biosensing Applicationmentioning
confidence: 99%
“…
Fig. 11 a Au@PGlyco SERS spectra [ 126 ]. b orientation and immobilization of O -cyanate chain-end functionalized sialyllactose-containing glycopolymers for microarray and SPR applications via isourea bond formation [ 127 ]
…”
Section: Glycopolymer-based Biosensing Applicationmentioning
confidence: 99%
“…The evasion of immune surveillance and programmed cell death are two important factors that promote BC progression. Despite the utility of active intervention by transurethral resection and intravesical bacillus Calmette-Guérin (BCG) [ 2 , 3 ], which could partially suppress BC progression, 20% of patients still developed muscle-invasive BC and were insensitive to monotherapy [ 4 ]. Unfortunately, programmed death-ligand 1, a coinhibitory factor of the immune response, is highly expressed in BC, resulting in an immunosuppressive “cold tumor” environment that diminishes immunotherapy efficacy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, designing a multitarget treatment strategy could provide new insights into eradicating BC progression. Recently, there has been widespread interest in the development of new theranostic nanoagents for exploring a noninvasive treatment modality for BC, which could enhance detection and therapeutic efficiency because the unique crosstalk of the cellular response to active uptake, penetration, and circulation relies on the size and shape effects of small particles [4,[7][8][9][10][11][12][13]. The extensive surface chemistry of nanoparticles as a result of surface modification, in contrast to the complicated synthesis of organic derivatives, is beneficial for the targeted delivery of drugs to achieve high accumulation in a lesion and prevent clearing by the reticuloendothelial system [8,9,12].…”
Section: Introductionmentioning
confidence: 99%